Potentiality of some Sudanese Acacia species for nodulation and nitrogen fixation - ElTahir, Inaam; Babiker, Hashim; Mukhtar, Nouri; Hamad, Muawia (Gezira Journal of Agricultural Science, 2010)
Pot experiments were carried out to investigate the capability of seven Acacia species ( A. seyal , A. senegal , A. nilotica , A. polycantha, A. mellifera , A. nubica and A. tortilis ) for nitrogen fixation and to assess the efficiency of isolated and re-inoculated rhizobia for nodulation and N fixation. Also, the amount of N fixed by four Acacia species ( A. seyal , A. senegal , A. mellifera and A . nubica ) was estimated using 15 N isotope dilution method with Tamarindus indica used as a reference plant. Fertilization was carried out by adding 20 kg N/ha (5% 15 N atom excess) and 100 kg N/ha (1% 15 N atom excess) to the fixing and to the non-fixing plants, respectively. Dry biomass, number of nodules, dry weight of nodules, N% and N content were determined. Plant tissue analysis was carried out for 15 N and 14 N. Result showed significant differences between the species in the growth parameters, with Acacia polycantha, A.seyal and A. mellifera giving the highest values. The inoculated plants gave the highest biomass and nodulation parameters. The study revealed a strong relationship between biomass and N content. The study also showed differences in N fixation among the tested Acacias  species( A . nubica , A . senegal , A . mellifera and A . seyal ) both in terms of % N needed by the plant (60%, 58%, 53% and 50%)  and the total N fixed (0.063, 0.104, 0.098 and 0.078 g/plant, respectively).    أجريت ثلاث تجارب في أصص  لإختبار مقدرة بعض الأشجارالبقولية من جنس الأكاسيا (الطلح والكتر والهشاب والسنط والكاكاموت والسيال واللعوت) لتثبيت النيتروجين الجوى ولإختبار قابلية الباكتيريا من نوع الريزوبيا للمعيشة التكافلية مع أشجار الأكاسيا. كما تم تحديد كمية النيتروجين المثبتة بواسطة بعض الأنواع (الكتر والهشاب والطلح واللعوت) بإستعمال العرديب كنبات مرجعي لحساب كمية النيتروجين  بإستعمال نظير النيتروجين 15N. تمت إضافة 20 ( 5%فوق المعدل الطبيعي) و 100 ( 1%فوق المعدل الطبيعي) كجم نيتروجين/ هكتار لكل من الأشجار البقولية والغير البقولية على التوالي. أخذت قراءات الوزن الجاف للكتلة الحية، عدد ووزن العقد البكتيرية كما تم تحليل النباتات لتحديد نسبة النيتروجين و المحتوى النيتروجيني للنبات. في التجربة الأخيرة تم تحليل أنسجة النباتات لتحديد محتوى نظائرالنيتروجين  15N و14N. في تجربتي مقدرة أشجار الأكاسيا علي تثبيت النيتروجين و تكافلية الباكتيرية العقدية للمعيشة معها أثبتت الدراسة أن هناك فروقاً معنوية في القراءات المختلفة بين أنواع الأكاسيا المختلفة. كما أثبتت الدراسة أن الكاكاموت والكتر والطلح أعطت أعلي القراءات. أثبتت التجارب أن الشتول الملقحة بالباكتيريا أعطت أعلي قراءات للوزن الجاف للكتلة الحية.كما أعطت الأنواع الأكثر وزنٵ جافٵ للكتلة الحية أعلي محتوى نيتروجيني. سجلت أنواع الأكاسيا المختلفة نسب تثبيت نيتروجين مختلفة (اللعوت 60% والهشاب 58% والكتر53% والطلح 50% من إحتياج النبات الفعلي) و كان وزن النيتروجين الكلي المثبت 0.063 و 0.104 و0.098 و 0.078 جم/نبات علي التوالي.